Memory, art and intergenerational transmission: Artistic practices with young people in memory sites in Argentina - Tornay, Lizel (2022)
This text analyzes recent experiences with young people from Middle Schools of the city of Buenos Aires (Argentina) in Memory Sites of this city. Our inquiry is interested in the intergenerational transmission referring to the traumatic past around the last military dictatorship established in Argentina between 1976 and 1983. With this interest, two experiences designed through artistic languages are analyzed: the Posters Project from the Memory Park and the use of poetry in the guided visits to the Memory Site at "El Olimpo", former Clandestine Detention Center for Torture and Extermination, both spaces of the city of Buenos Aires.